Analysis of Student Obstacles in Online Learning - Hendra Dani Saputra; Wawan Purwanto; Alfiza Candra; Dwi Sudarno Putra; M Yasep Setiawan; Ahmad Arif (VANOS Journal of Mechanical Engineering Education, 2023)
This study presents an analysis of students' condition in online learning in the autotronics technology course of the Department of Automotive Engineering, Universitas Negeri Padang. This research aims to find obstacle to online learning based on technology, human and environmental factors. This research is a quantitative descriptive study. The subjects of this study were 120 students who took the autotronics technology course at Universitas Negeri Padang, Department of Automotive Engineering, Faculty of Engineering in the 2019/2020 semester. A questionnaire using a Likert scale was used for data collection. Analysis techniques use descriptive analysis techniques and confirmatory factors. The results of confirmatory factor analysis, factors were formed that could explain 76.84% of the variance of the original variables. The human side is the biggest hurdle. 77 of 120 students were less enthusiastic about participating in bold learning, 86 of 120 students struggled to understand the material being bravely taught, and 93 of 120 students had difficulty understanding charts and series in the material, and 87 out of 120 students had difficulty understanding the material. It was difficult to understand the material without doing the lab. The human variable is considered the biggest constraint compared to other variables studied. These constraints are the personality indicators and intelligence indicators.